Pre-Study on the Development of Internet of Things-Based Prototype Data Logger for Measuring Heat Sufficiency Number - Syukri, Daimon; Rini; Deden Dermawan Septina; Rudi Alfiansyah; Aurelia Amaliyah Tarumiyo; Yasmin Azzahra; Dendi Adi Saputra (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2025)
This study aimed to develop an IoT-based data logger prototype to improve data acquisition and monitoring during the sterilization process. Achieving an adequate heat sufficiency value, commonly known as the F0 value, was crucial for effective sterilization, and a thermocouple sensor was typically employed for temperature recording. The research involved designing, constructing, and testing the prototype with a focus on enhancing durability and functionality. Key improvements included adding waterproof sealants to prevent leakage, integrating connectors for enhanced connectivity, and coating the sensor's connector end to ensure long-term performance. Performance evaluation compared the improved IoT data logger with a conventional data logger in terms of heat penetration measurement. Results showed that the IoT prototype recorded heat penetration data with comparable accuracy to the conventional system, confirming its reliability for practical application. The bias for the difference was less than 10%. This innovation demonstrated the potential for improved monitoring in sterilization processes, contributing to enhanced process control and product safety.